1974
DOI: 10.1007/bf01097626
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and remyelination ofXenopus tadpole optic nerve fibres following transection or crush

Abstract: Optic nerves of stage 54-56 Xenopus laevis tadpoles were either transected or crushed, and subsequent Wallerian degeneration, regeneration, and remyelination were examined. After 4 days, normal myelinated fibres were no longer present in the distal stump, and only a few unmyelinated fibres remained. After 10-13 days, the distal nerve consisted mainly of a core of reactive astrocytes with enlarged processes and scattered oligodendrocytes which persisted throughout the degenerative period. Regenerating axons tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(59 citation statements)
references
References 44 publications
4
55
0
Order By: Relevance
“…Evidence that the glial scar is differentially repulsive depending on the species was demonstrated most convincingly by Reier, who showed that regeneration can occur directly through a glial 'scar' in amphibians 137,138 . In these studies, the optic nerve of Xenopus was repeatedly crushed and the dense reactive glial tissues that were induced were harvested and transplanted near the freshly severed optic stump of a recipient.…”
Section: Box 2 | Cold-blooded Species Can Regenerate Their Axonsmentioning
confidence: 96%
“…Evidence that the glial scar is differentially repulsive depending on the species was demonstrated most convincingly by Reier, who showed that regeneration can occur directly through a glial 'scar' in amphibians 137,138 . In these studies, the optic nerve of Xenopus was repeatedly crushed and the dense reactive glial tissues that were induced were harvested and transplanted near the freshly severed optic stump of a recipient.…”
Section: Box 2 | Cold-blooded Species Can Regenerate Their Axonsmentioning
confidence: 96%
“…In the amphibian, for example, hypertrophic astrocytes form a scar within the degenerated, central stump of the nerve. In contrast with the inhibitory effect that mammalian astrocytes appear to exert on fiber elongation (e.g., Aguayo et al, 1978;David and Aguayo, 1981; for further discussion, see Kiernan, 1979;Reier et al, in press), this region of gliosis in the amphibian does not impede axonal elongation (Reier and Webster, 1974;Turner and Singer, 1974;Stensaas and Feringa, 1977;Reier, 1979;Scott and Foote, 1981).…”
mentioning
confidence: 88%
“…Thus far, most studies of optic nerve regeneration and functional recovery in the fish and amphibian have focused on the interactions between regenerating fibers and their surrounding cellular environment at levels central to a crush or transection site. Only a few, brief descriptions of neuritic elongation through the mesodermal matrix of completely severed optic nerves in these species have been presented (Sperry, 1943;Maturana, 1958;Attardi and Sperry, 1963;Gaze and Jacobson, 1963;Reier and Webster, 1974;Maloney, 1976). In some cases, aberrant axonal outgrowth after opticnerve injury has been observed (Gaze, 1959;Reier ar_d Webster, 1974;Tay and Straznicky, 19801, and the suggestion has been made that physical factors may direct the elongation of axons in peripheral regions of the optic pathway.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Axonal sprouting [3,4], reorganization of con nections [5] or activation of alternative strategies [6] have been considered the neurobiological bases for recovery. In fish and amphibians severed optic axons are able to regen erate and establish new contacts in target tissue [7,8]. However, regeneration of axonal connections in the mam malian optic nerve is usually not seen, except under spe cific experimental conditions [9][10][11], In this case, the mammalian optic nerve behaves similarly to myelinated central nervous fiber bundles [12] and therefore provides an adequate and simple model for studying the effects of central nervous system (CNS) trauma.…”
mentioning
confidence: 99%